Cinta dan Problem Moralitas dalam Islam - Mohammad Rofiq (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2021)
There are various kinds of natural love that exist in humans: romantic love, love for children and parents, love for the beauty of art and nature, love for knowledge, and even love for power, wealth and fame, all of which, because of worldly interests, can harm humans themselves. In Islam, all worldly love must pivot on divine love. All love that negates and we humans from God is an illusion that can lead to the collapse of the soul. Love is perceived, appreciated, and actualized according to the level of appreciation and ability to understand the object he loves. Love is the happiness that gives birth to all. Love that is straight axis God will give birth to compassion, honesty to, love, loyalty, justice, equality, freedom, creativity, achievement and other qualities of perfection.